An analysis on perception of university students toward childfree marriage - Mohamed Sadique, Raziah Bi; Musman, Musliha; Muda, Salwa; Ismail, Norhidayah; Idris, Asma' Rashidah (2025)
Childfree has become an increasingly preferred choice among married couples, and this growing trend may significantly affect national demographics by shrinking the working-age population, raising dependency ratios, and placing greater financial strain on social support systems, ultimately challenging sustainable economic growth. This study explores the perceptions and key factors influencing the childfree choice among Malaysian youth, with university students from Universiti Teknologi MARA (UiTM) Negeri Sembilan serving as the respondents. Employing a quantitative approach, data were gathered from 217 participants across three campuses to examine the impact of economic, career, health, and lifestyle factors on their reproductive decisions. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) Version 29.0. The findings indicate that health and lifestyle significantly shape the decision to be childfree, whereas economic and career factors do not show a significant effect. The results suggest that students value personal freedom, independence, and quality of life, viewing parenthood as a potential limitation due to its time, financial, and lifestyle constraints. These insights reflect a generational shift from traditional beliefs linking childbearing to financial or career stability. This study contributes valuable empirical evidence on the changing reproductive attitudes of Malaysian youth, offering important implications for policymakers, educators, and social planners in responding to emerging demographic and societal trends.